PERFORMANCE OF CONCRETE WITH PARTIAL REPLACEMENT OF FINE AGGREGATES WITH CRUSHED WASTE GLASS (Nigerian Journal of Technology, 2017)
Aggregate, both fine and coarse are major components of concrete.  The cost of these aggregates is on the increase. There is also a serious environmental concern for the disposal of waste glass world-wide.  These factors are major thrusts of this study- the investigation of crushed waste glass as partial replacement of fine aggregate in concrete, with a view to protecting the environment and also reducing the cost of concrete. The study investigated the level of replacement of fine aggregate with waste glass that will result in optimal compressive strength. A total of 36 cubes were cast. 6 cubes without waste glass (control) and 30 cubes containing waste glass as partial replacement for fine aggregates at 15%, 25%, 35%, 45%, and 50%. Water/cement ratio of 0.6 was used. The concrete cube samples were cured and tested at 7 and 28 days respectively for compressive and flexural strength, water absorption and light weight character. Compressive strength were found to increase by 3% and 7% at  7 and 28 days respectively as waste glass content was increased up to 15% replacement level, after which the compressive strength started to decrease. Flexural strength remained constant between the control value and 15% replacement level, after which it started to fluctuate, (decreasing by 25% and 47% at 25% replacement level at 7 and 28 days, and experienced an increase of 33% and 37.5% at 35% at replacement level.  Water absorption of the concrete decreased as the waste glass content increased. Initial and final setting times decreased as the waste glass content increased, while the workability of the concrete increased as the waste glass content increased and started to experience a decrease at 35% waste glass replacement level.http://dx.doi.org/10.4314/njt.v36i2.12